THE INFLUENCE OF ACCOUNTING STANDARDS, TECHNOLOGY AND LOCAL APPARATUS ON THE FINANCIAL REPORTING OF BPKAD IN BANDUNG CITY - Prasetya, Cecillia Ayu; Rapina, Rapina (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2024)
The purpose of this study is to determine the influence of the application of government accounting standards, the utilization of technology and the quality of local government apparatus on the quality reports of the Bandung City BPKAD Financial Reporting (BPKAD). This study combines several variables, namely, the variables of application standard accountancy governance (X1), utilization technology (X2), and quality apparatus government area (X3) against quality report finance (Y). The researchers took samples using purposive sampling technique. The results showed that the implementation of the government accounting standard has a significant positive effect on the Quality of financial reports. The use of technology has an important positive effect. The quality of the local Government Apparatus government area has an obvious positive effect, and the use of information technology can assist government entities in compiling and producing quality financial reports effectively, efficiently, and economically. It is important to pay more attention to the competency of the human resources of government employees. For the local government of Bandung city, it is advised to further improve the quality, relevance, and understandability of the financial statements produced so that financial reports can be presented in a timely manner. The SKPD level needs to be considered, as they greatly assist employees in performing their duties effectively.